Stereospecific Assay of (R)- and (S)-Goitrin in Commercial Formulation of Radix Isatidis by Reversed Phase High-Performance Liquid Chromatography - Lixing Nie; Zhong Dai; Shuangcheng Ma (Journal of Analytical Methods in Chemistry)
Radix isatidis (Banlangen) is a widely used traditional Chinese medicine for treating fever and removing toxic heat. Pharmacological studies have indicated that (R)-goitrin (epigoitrin) is one of the main constituents accounting for its antiviral activity, while (S)-goitrin (goitrin) is known as an antithyroid factor. To better control the quality of radix isatidis and its formulations, it is imperative to enantiomerically determine the contents of R- and S-goitrin. In this study, an enantioselective method based on reversed phase chromatography was developed for the assay of (R, S)-goitrin enantiomers. Optimum separation was obtained on an S-Chiral A column (4.6 mm × 250 mm, 5 μm) using methanol/water (30 : 70, v/v) as the mobile phase. After validation, the method was applied to quantify the enantiomers in Banlangen granules, which is the most prescribed commercial formulation of radix isatidis. Compared to enantioselective resolution approaches based on normal phase chromatography, the new method could be conveniently performed using regular reversed phase high-performance liquid chromatography (RP-HPLC) equipment and was found to be more suitable for the enantioselective quality control of water-extracted and soluble medicines.